Nitrogen addition substantially affects plant phenology in terrestrial ecosystems: a meta-analysis - He, Yaqi; Zhou, Tenglong; Mao, Jianing; Li, Mengke; Sun, Ruomin; Liu, Chang; Li, Wen; Ma, Lei; Fu, Shenglei (Frontiers in Plant Science, 2025)
IntroductionPhenology is a sensitive biological indicator of climate change. Increasing nitrogen (N) deposition has amplified phenological shifts, making their study across terrestrial ecosystems crucial for understanding global change responses. While existing research focuses on single ecosystems, comparative analyses are lacking.MethodsOur meta-analysis of 125 species across different ecosystems examined the effects of nitrogen addition on various phenological stages.ResultsThe results showed that nitrogen addition advanced flowering by 0.18 days but delayed budding (4.15d), leaf fall (4.95d), fruiting (0.21d), leaf discoloration (1.5d), maturity (3.3d), senescence (4d), and xylem growth (8.56d). In summary, nitrogen addition remarkably affects terrestrial ecosystems by delaying most phenological stages of plants. Additionally, some climatic factors also significantly influence phenological stages. A positive correlation exists between temperature elevation and the advancement of key phenological stages (e.g., flowering) in forest ecosystems, while temperature, precipitation, and nitrogen addition had little effect on the phenology of grassland and farmland plants.DiscussionThis is because different ecosystems have different functions, resource allocation, and climate adaptation strategies, resulting in different responses to different environmental factors. Thus, future research should focus on how global changes affect the phenology of plants in different ecosystems rather than in single ecosystems.